Стан центральної гемодинаміки, варіабельності серцевого ритму та фізичної працездатності у гандболістів екстра-класу - Михалюк, Євген Леонідович; Mikhalyuk, Ye. L. (My University, 2009)
Heart rate variability, central hemodynamics and physical capacity for work indices have been studied in 44 handballers, 15 of them are sportsmen of MSIC level and 29 are MS level. Comparison of the indices studied depending on the sport qualification as well as on the optimum values of central hemodynamics (CI, CCR) and heart rate variability (EI, LF/HF) is presented.
Central hemodynamics, heart rate and physical capacity for work in extra-class handballers